Sinusite recorrente de causa incomum - Meirelles,Roberto Campos (1999)
The authors present a case of chronic recurrent sinusitis of rare etiology in a man submitted previously to a facial peeling. The computed tomography and the sinusal endoscopy revealed periorbital fat in the maxilary sinus. There was a history of old orbital floor fracture.